"Acesso restrito” análise do racismo institucional em unidades de saúde pública em Crato-CE - Gomes, Hayane Mateus Silva (2016)
The proposition of this research is to analyse the institucionalized racism on the public healt specialized unitof Crato; to understand the relationship and relevance. To think about the reality of the health for the Afro- descendant population in the municipality. It is also an attempt to understand how the various segments that work with healt and the black population that uses It conceive this theme. In this sense, it seeks to analyze the health institutions work has as main method the analysis of semi- structured interviews with municipal managers, coordinators of health facilities, professionals and patients. Finally, those of African descent are far from benefiting fully the rights granted to them, to denounce many situations negligence, constraints and discrimination in public facilities, demonstrate the effectiveness of institutional racism, the narratives of black patients compared to white patients out this well.